2003
DOI: 10.1076/orbi.22.3.199.15619
|View full text |Cite
|
Sign up to set email alerts
|

Laser conjunctivoplasty: A new technique for correction of mild medial ectropion

Abstract: Thirty patients with mild medial ectropion of the lower lid were treated by Argon green laser. A diamond-shaped area (6 x 4 mm in size) on the medial part of the tarsal conjunctiva of the lower lid was burnt with overlapping spots until white blanching and visible contraction of tissue were seen. The apex of the diamond was kept 4 mm below the punctal opening. After an average follow-up of 6 months, functional success was achieved in 22/30 eyes. Anatomical success in terms of repositioning of the punctum was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…[ 21 ] Furthermore, a study on medial ectropion repair using palpebral laser conjunctivoplasty indicated that laser-induced conjunctival shrinkage is safe since it does not induce excessive conjunctival burns or scarring. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] Furthermore, a study on medial ectropion repair using palpebral laser conjunctivoplasty indicated that laser-induced conjunctival shrinkage is safe since it does not induce excessive conjunctival burns or scarring. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[21] Furthermore, a study on medial ectropion repair using palpebral laser conjunctivoplasty indicated that laser-induced conjunctival shrinkage is safe since it does not induce excessive conjunctival burns or scarring. [22] Conjunctival shrinkage may reduce its redundancy, and conjunctival coagulation may reinforcement the conjunctival attachment to the globe, reducing conjunctival laxity. [23] The photothermal mechanism underlying CCh shrinkage induced by the argon laser is similar to that of a thermal cautery device or high-frequency radiowaves.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, using of argon laser without excision of tissue, or the use of full-thickness everting sutures has been described only at 2003 by Nainiwal S, and co-authors [ 17 ] and achieved good functional results by relief of symptoms in 22 (73%) eyes, and an acceptable anatomical outcome with repositioning of the punctum in 24 (80%) eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Argon lasers have been used for laser conjunctivoplasty 12,13 . However, they work at a wavelength of 532 nm and the laser energy is primarily absorbed by blood and can lead to vessel rupture and hemorrhage.…”
Section: Introductionmentioning
confidence: 99%